The Effectiveness of a Ketso Strategy in Developing Reading Comprehension Skills of Seventh-Grade Students in Jordan - Al-Hawamdeh , Mohammad (Dirasat: Educational Sciences, 2021)
This study aims at examining the effectiveness of the Ketso strategy in developing reading comprehension skills of Seventh-grade students at King Abdullah II School for Excellence in Irbid Governorate during the first semester in the academic year 2019/2020. The sample of the study consisted of 50 male students who were divided randomly into two groups: (24 students) in the experimental group taught by the Ketso strategy, and (26 students) in the control group taught by the conventional method. To obtain the data of the study, the researcher applied a reading comprehension pre/post-test after testing its reliability and validity. The results of the study revealed that there was a statistically significant difference in the level of performance of the participants’ reading comprehension skills in favor of the experimental group. A number of recommendations were put forth in light of the results of the present study.